Sevoflurane-Based Inhalation Induction in High-Risk Elderly Patients During Noncardiac Surgery - O. A. Grebenchikov; A. S. Murachev; D. I. Levikov; D. D. Selivanov; V. V. Likhvantsev (Общая реаниматология)
Objective: to study the hemodynamic effects of sevoflurane during the induction of anesthesia in elderly patients at high risk for cardiac events. Subjects and methods. This study enrolled 32 patients who had a left ventricular ejection fraction of <30% during preoperative examination. According to the presumptive type of anesthesia, the patients were randomized to one of the study groups: In the sevoflurane group receiving infusion of fentanyl (1 ig^kg”‘^hr”‘), anesthesia was induced by sevoflurane at the maximum concentration of 8 vol% at first inspiration, without the respiratory circuit being prefilled. After loss of consciousness, further saturation was carried out using Fianesth, 5 vol%. Combination anesthesia (CA) was that which was induced by successive administration of dormicum, ketamine, propo-fol, and fentanyl. The trachea was intubated during total myoplegia under the control of TOF (TOF-Watch, Organon, the Netherlands). Results. In all the patients under CA, its induction was made during infusion of dopamine (5 lg^kg”‘^min”‘), the dose of which had to be increased up to 10 ig • kg-1 • min-1 in 6 (75%) patients. Nevertheless, there were decreases in mean blood pressure (BPmean) to 46±6 mm Hg and in cardiac index (CI) to 1.5±0.3 fig • kg-1 • min-1 (by 32% of the outcome value). In the sevoflurane inhalation induction group, only 3 (12.5%) patients needed dopamine. Its dose producing a cardiotonic effect was near-minimal; its average maintenance infusion rate was 5.3±0.3 ig^kg”‘^min”‘. The reduction in CI was statistically insignificant; despite a 9% decrease in BPmean, this indicator in the sevoflurane group remained within acceptable ranges. Conclusion. The use of a sevoflurane-based inhalation induction technique permits higher hemodynamic stability in patients at high risk for cardiac events. Key words: inhalation induction, sevoflurane, ketamine, elderly patients.